Izkušnja doživljanja kronične bolezni in strategije soočanja z njo - Kregelj, Lena (Družboslovne razprave, 2015)
The article focuses on a personal experience of dealing and coping with a chronic disease. We focused on the question of how a patient's strategies for coping with a chronic disease are defined and, second, on which factors do styles of adjusting to the disease depend. This article is based on the results of quantitative and qualitative research in patients with chronic rheumatic disease. There are two different subgroups of patients that may be differentiated on the basis of social inclusion, their approach to problem-solving and the intensity of how they have adapted their lifestyle to the requirements of the disease. The friendliness of the social environment and having an emphatic relationship with people close to a patient can significantly impact on the patient's successful adaptation to the disease.
Keywords: Sociologija vsakdanjega življenja; Sociology of everyday life; Zdravje; Health; Kronične bolezni; Chronic diseases